(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The article considers the political «weight» of the civil agenda, i.e. political alternatives to the domestic political course in modern Russia. Based on the expert survey data and secondary information, the author shows the changes in the current political agenda in 2019. Agenda was framed by the constitutional reform announcing in 2020. It was a response to the expectations of changes among Russian people. From the other hand that was an attempt by the government to “catch the agenda” blocking the non-systemic opposition. That was plan to demobilize its supporters by involving them in the discussion about constitutional amendments